Synthesis and characterization of an orally bioavailable small molecule agonist of the apelin receptor. (15th July 2022) - Narayanan, Sanju; Dai, Donghua; Vyas Devambatla, Ravi Kumar; Albert, Vincent; Bruneau-Latour, Nicolas; Vasukuttan, Vineetha; Ciblat, Stephane; Rehder, Kenneth; Runyon, Scott P.; Maitra, Rangan
Graphical abstract: Abstract: The apelin receptor (APJ) is a target for cardiovascular indications. Previously, we had identified a novel pyrazole-based agonist 1 (( S )- N -(1-(cyclobutylamino)-1-oxo-5-(piperidin-1-yl)pentan-3-yl)-1-cyclopentyl-5-(2, 6-dimethoxyphenyl)-1 H -pyrazole-3-carboxamide hydrochloride) of this GPCR. Systematic modification of 1 was performed to produce compounds with improved potency and ADME properties. Orally bioavailable compound 47 with favorable agonist potency (Ca 2+ EC50 = 24 nM, cAMPi EC50 = 6.5 nM) and pharmacokinetic properties (clearance ∼20 mL/min/kg in rats) was identified. This compound has vastly reduced brain penetration and is devoid of significant off-target liability. In summary, a potent and selective APJ agonist suitable for in vivo studies of APJ in peripheral tissues after oral administration has been identified.